Dampak Perkembangan Teknologi Artificial Intelligence Terhadap Pelajar dan Mahasiswa - Bagus Angkasawan Sumantri Putra; Muhammad Gilang Ramadhan; Rangga Andhika Pratama (LPPM Universitas Pramita Indonesia, 2023)
This research aims to identify the impact of artificial intelligence (AI) technology development in the world of education, especially on students. The research was carried out using quantitative methods with questionnaires through Google Forms that were distributed online to various social media. The data uses a variety of past studies related to this topic. The results showed that the development of artificial intelligence technology has made AI increasingly common in society, especially students, although many still do not understand the concept and how it works. However, the research also reveals that the use of AI in education provides significant benefits, such as personalized learning, individual progress monitoring, and instant feedback provision. Moreover, the adoption of AI in education is found to enhance the efficiency of the learning process and assist students and learners in developing cognitive and social skills. Nevertheless, the research highlights several challenges that need to be addressed, including ethical concerns, data privacy, and a lack of in-depth understanding of AI. The results of this research are expected to provide valuable insights for education stakeholders in effectively and responsibly harnessing artificial intelligence technology. Keywords: technology, artificial intelligence, education, student, development